Učenje nemškega sestavljenega preteklika 'Perfekta' skozi različne didaktične pristope - Godler, Urška (Revija inovativna pedagogika, 2025)
This paper presents teaching methods for the German past tense Perfekt in Grade 8, which helps learners expand their language skills and improve their everyday communication. The paper's main aim is to show the process of learning Perfekt using different didactic approaches and digital tools and to develop both their linguistic and digital competencies. Aimed at foreign language teachers, this article provides a valuable example of the use of different didactic approaches, both 'analog' and 'digital,' to introduce new material. A descriptive method is used to describe the individual learning steps in conjunction with a qualitative methodology (case study). Qualitative data was collected by observing the learners in solving exercises, reviewing texts composed by pupils, watching films made by pupils, and evaluating them according to specific criteria. We found that pupils successfully mastered the correct formation of the Perfekt with both regular and irregular verbs. Despite their progress, learners still made errors, indicating that further training using a variety of didactic approaches is needed to fully master the Perfekt. Learners developed linguistic and digital competencies in information and data literacy, communication, and collaboration based on face-to-face interaction between pupils using digital technologies and digital content creation.
Keywords: Digitalna pismenost; interactive exercises; interaktivne vaje; learning cards; Osnovnošolsko izobraževanje; Perfekt; sestavljeni preteklik; učne kartice